Perbedaan Adversity Quotient ditinjau dari Coping Stress dan Self Efficacy - Diny Atrizka; Kevin Sanjaya; Dea Vanthera; Wulandari Wulandari; Khrisna Sanubari Limbong; Rizky Yusfasari (Psyche 165 Journal, 2020)
This study aimed to determine the difference adversity quotient in terms of coping stress and self-efficacy of tenth grade students in SMA Swasta Medan. The population of this study was all of the students of tenth grade in SMA Swasta Medan. The subjects used in this study were 146 students who were selected using the disproportionate stratified random sampling method. This study was a comparative quantitative, data collected used Likert Scale which is adversity quotient (AQ), coping stress (CS), and self-efficacy (SE) scale. In this study the data analysis technique used is analysis of varians (ANOVA). The assumptions test consisted of an normality test, a homogenity test, and a hypothesis test.The result of data analysis showed a significant difference adversity quotient in terms of coping stress with Sig .000 < p = .05 and a significant difference adversity quotient in terms of self-efficacy with Sig .000 < p = .05 that owned by the students. The conclusion obtained from this study is a proven hypothesis, namely the difference between adversity quotient (AQ) in terms of coping stress (CS) and adversity quotient (AQ) in terms of self-efficacy (SE), where the contribution percentage of coping stress (CS) in influencing adversity quotient (AQ) was 16.6% and self-efficacy (SE) in influencing adversity quotient (AQ) was 19.5%, the rest was developed by other factors that were not appropriate by the researcher.